On the optimal control force applied to tuned mass dampers for multi-degree-of-freedom systems - Anh, Nguyen Dong; Sang, Nguyen Chi (Vietnam Journal of Mechanics, 2004)
The design of active TMD for multi-degree-of-freedom systems subjected to second order coloured noise excitation is considered using the linear quadratic optimal theory. A detailed numerical study is carried out for a 2-DOF system. It is shown that the effectiveness of active TMD is better than the one of passive TMD.